An economic assessment of the Philippine eucheuma seaweed industry with implications for future policy. - Hollenbeck, Leroy Frank (University of Hawaii, 1983)
A Thesis submitted to the Graduate Division of the University of Hawaii in Pasrtial Fulfillment of the Requirements for the Degree of Master of Science in Agricultural and Resource Economics, August 1983